Effectiveness of Implementing Research-Based Learning Models in Islamic Religious Education on Developing Critical Thinking and Creativity - Alya Riskiya; Muhlisin Muhlisin; Rahmi Anekasari (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
The rapid development of information technology and digital communication in the twenty-first century requires students to possess critical thinking and creativity skills, particularly in Islamic Religious Education (PAI). This study aims to examine the effectiveness of Research-Based Learning (RBL) in fostering students’ critical thinking and creativity within PAI learning contexts. The study employed a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework. Data were collected from Google Scholar through the Publish or Perish application, focusing on publications published between 2021 and 2026. Following the identification, screening, eligibility, and inclusion processes, eight relevant studies were selected for analysis. The findings indicate that RBL is effective in enhancing students’ critical thinking, creativity, analytical reasoning, problem-solving abilities, independent learning, and active participation in learning activities. The reviewed studies consistently demonstrate that RBL encourages students to formulate problems, investigate evidence, analyse information, and construct arguments related to religious and socio-religious issues. This study contributes to the growing body of literature by synthesising recent empirical evidence on the implementation of RBL in Islamic Religious Education across various educational levels. However, the review is limited to studies indexed in Google Scholar and published within the 2021–2026 period. Future studies are recommended to employ broader databases and empirical research designs to further examine the long-term impact of RBL on students’ cognitive, affective, and behavioural development in Islamic education.